Obat Tradisional dalam Pusaran Globalisasi: Tinjauan Literatur Standarisasi, Validasi Ilmiah, dan Tantangan Biopiracy - Aminudin; Andini, Claudya; Atriani, Iis; Pebriani, Lilis (Pharmaceutical Journal, 2025)
Traditional medicine has been an integral part of the community medicine system and has been passed down from generation to generation, and is now even more relevant in the midst of globalization. The increasing interest in herbal medicine cannot be separated from the public's concerns regarding the side effects of chemical drugs and the need for a more holistic approach to health. However, the development of traditional medicine faces quite complex challenges, ranging from the lack of standardization, limited scientific validation, to the threat of biopiracy against genetic resources and traditional knowledge. This paper seeks to analyze the literature that discusses pharmaceutical standardization efforts, scientific validation, and protection strategies against biopiracy in the development of traditional medicines.